Using stable Mg isotope signatures to assess the fate of magnesium during the in situ mineralisation of CO2 and H2S at the CarbFix site in SW-Iceland - Oelkers, EH; Butcher, R; Pogge von Strandmann, PAE; Schuessler, JA; von Blanckenburg, F; Snæbjörnsdóttir, S; Mesfin, K; Aradóttir, ES; Gunnarsson, I; Sigfússon, B; Gunnlaugsson, E; Matter, JM; et al. (2019)
The in-situ carbonation of basaltic rocks could provide a long-term carbon storage solution. To investigate the viability of this carbon storage solution, 175 tonnes of pure CO2 and 73 tonnes of a 75% CO2-24% H2S-1% H2-gas mixture were sequentially injected into basaltic rocks as a dissolved aqueous fluid at the CarbFix site at Hellisheidi, SW-Iceland. This paper reports the Mg stable isotope compositions of sub-surface fluids sampled prior to, during, and after the CO2 injections. These Mg isotopic compositions are used to trace the fate of this element during the subsurface carbonation of basalts. The measured Mg isotopic compositions of the monitoring well fluids are isotopically lighter than the dissolving basalts and continue to become increasingly lighter for at least two years after the gas-charged water injection was stopped. The results indicate that the formation of isotopically heavy Mg-clays rather than Mg-carbonates are the predominant Mg secondary phases precipitating from the sampled fluids. Isotope mass balance calculations suggest that more than 70% of the Mg liberated from the basalt by the injected gas charged water was precipitated as Mg-clays, with this percentage increasing with time after the injection, consistent with the continued precipitation of Mg clays over the whole of the study period. The formation of Mg clays in response to the injection of CO2 into basalts, as indicated in this study, could be detrimental to carbon storage efforts because the formation of these minerals consume divalent Mg that could otherwise be used for the formation of carbonate minerals and because such clays could decrease host rock permeability.